Islam Maritim dan Kultur Penjelajah Laut Masyarakat Nusantara - Hamdani, Hamdani; Masudi, Idris; Muhtarom, A. (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2023)
Studies on Southeast Asian Islam tend to analyze the culture of landed population rather than ocean and littoral-based dwellers. When in fact, the ocean landscape is more extensive and its culture has harbored many dramatic events in the course of human history. Through oceans and their surrounding places of cultural formation, Islam has grown and developed with local cultures in the mutual relation. This study attempts to identify manifestations of Islam among Southeast Asian seafarers Muslim of archipelago in their daily life and historical context. By investigating the experience of Eastern Indonesian seafarers such as the Bugis, Makasar, Mandar, Buton and Bajo people who have interacted with ocean life extensively, this study probes the process of Islamization and identifies the various ideas, practices, meanings and world-views of the Sea People in forging Islam and their culture. Based on the experience of Muslim agents who had a strong maritime ethos and focus on trade and proselytization in playing their social role, Islam and maritime culture have seemingly constituted two good relations to each other. The different reception and negotiation of Islam in maritime culture among Nusantara ethnic groups is interesting to analyze and help to conceptualize ‘Maritime Islam’ which has not been sufficiently studied by scholars to date. By combining secondary sources and field findings, this study explores the world-view of Nusantara Muslims and underscores the fact that Islam is not a single entity, but a plural and diverse phenomena.